Gene Expression Profile in the Liver of BALB/c Mice Infected with Fasciola hepatica. (2023)
Fasciola hepatica infection still remains one of the helminthic neglected tropical diseases (NTDs). It has a huge worldwide distribution, affecting mainly cattle and, sometimes, human beings.